Ischemia-Modified Albumin May Be a Novel Marker for Predicting Neonatal Neurologic Injury in Small-For-Gestational-Age Infants in Addition to Neuron-Specific Enolase - Tayman, Cuneyt; Öztekin, Osman; Serkant, Utku; Yakut, Ibrahim; Aydemir, Salih; Kosus, Aydın (American Journal of Perinatology, 2017)
Aim This study aims to evaluate hypoxia/ischemia and oxidant stress, and negative neurodevelopmental outcomes in small-for-gestational-age (SGA) infants.Material and Methods Two study groups were established as SGA and appropriate-for-gestational-age (AGA) infants. SGA infants were allocated asymmetric and symmetric SGA infants. Serum levels of neuron-specific enolase (NSE), ischemia-modified albumin (IMA), malondialdehyde (MDA), total antioxidant capacity (TAC), and total oxidant status (TOS) were determined and oxidative stress indexes (OSI) were calculated in all groups.Results Overall, 83 infants were diagnosed SGA, and 85 infants were determined AGA. TOS and OSI levels were significantly higher and TAC levels were significantly lower in SGA group (p < 0.05). MDA and IMA levels were significantly higher in SGA group (p < 0.05). NSE levels in SGA infants were significantly higher (p < 0.05). NSE and IMA were significantly higher in symmetric SGA infants (p < 0.05). TOS, OSI, MDA, TAC levels were not significantly different in SGA infants with abnormal neurological findings (p > 0.05); NSE and IMA levels were significantly higher in SGA group with abnormal neurological findings (p < 0.05).Conclusion SGA infants expose to hypoxia and oxidative stress led to neuronal damage. We suggest that in addition to NSE, IMA blood levels might be a sensitive novel marker for predicting the severity of neuronal damage.
Keywords: small-for-gestational-age; oxidative stress; neuron-specific enolase; ischemia-modified albumin; newborn